2018
DOI: 10.1074/jbc.ra118.002768
|View full text |Cite
|
Sign up to set email alerts
|

A TLR4-derived non-cytotoxic, self-assembling peptide functions as a vaccine adjuvant in mice

Abstract: Vaccination is devised/formulated to stimulate specific and prolonged immune responses for long-term protection against infection or disease. A vaccine component, namely adjuvant, enhances antigen recognition by the host immune system and thereby stimulates its cellular and adaptive responses. Especially synthetic Toll-like receptor (TLR) agonists having selfassembling properties are considered as good candidates for adjuvant development. Here, a human TLR4-derived 20-residue peptide (TR-433), present in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
(61 reference statements)
1
17
0
Order By: Relevance
“…These clearly indicated that the PVs without adjuvants have interacting domain to induce innate immune system. This is in agreement with the recent study where human TLR4-derived self-assembling peptide nanoparticles have been used as non toxic vaccine adjuvant with filarial antigenic protein to induce the immunological responses in mice [103].…”
Section: Molecular Docking Of Pvs With Receptors Tlr2 and Tlr4supporting
confidence: 92%
“…These clearly indicated that the PVs without adjuvants have interacting domain to induce innate immune system. This is in agreement with the recent study where human TLR4-derived self-assembling peptide nanoparticles have been used as non toxic vaccine adjuvant with filarial antigenic protein to induce the immunological responses in mice [103].…”
Section: Molecular Docking Of Pvs With Receptors Tlr2 and Tlr4supporting
confidence: 92%
“…agonists [78][79][80][81][82][83][84] was designed and validated to have overlapping B cell epitope regions through the IEDB server. The adjuvant sequences have been experimentally evidenced to generate neutralizing antibodies, cytokines and natural killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The triagonist chimeric adjuvant has the propensity to elicit immune responses to allow for its use as a suitable adjuvant against SARS CoV 2. RS09 [78], TR-433 [79] and a Mtb based Hsp70 partial sequence [80,81] were utilized in this endeavor. An appropriate rigid polar linker (DP) was utilized in this regard.…”
Section: Design Of Adjuvantmentioning
confidence: 99%
“…The triagonist chimeric adjuvant has the propensity to elicit immune responses to allow for its use as a suitable adjuvant against SARS-CoV-2. RS09 (Shanmugam et al, 2012), TR-433 (Tandon et al, 2018), and an MTB based Hsp70 partial sequence (Dabaghian et al, 2015;Reed et al, 2016) were utilized in this endeavor. An appropriate rigid polar linker (DP) was utilized in this regard.…”
Section: Design Of Adjuvantmentioning
confidence: 99%